The Effect of Incorporating a Human Capital's Analysis into Strategic Planning - Gandrita, Ana; Rosado, David Pascoal (Journal of Reviews on Global Economics, 2019)
This paper gains a better understanding about the relation between Business Strategy and Human Capital and of how the introduction of a clear human capital analysis in early stages of strategic planning impact Strategy Execution and the company's achieved results. The findings show that Human Capital and Business Strategy have an intimate relationship. In fact, through literature review, surveys and interviews we were able to understand not only that the alignment between a company's human capital and its outline strategy is critical for strategy implementation and execution but also that the use of a Human Capital Analysis, along with other management tools, in strategic planning helps to maximize the efficiency of achieved results, on one hand, by enabling to design more realistic and doable strategies, it helps to align the strategy with the company's human capital strengths and weaknesses in order to reduce the strategy execution GAP allowing maximizing the efficiency of achieved results and, on other hand, by enabling the right alignment between who defines the corporate strategy and who implements it, it helps the whole companyÂ´s human capital become more productive and productive people don't waste time or resources allowing maximizing the efficiency of achieved results. The study's conclusions point towards the need of rethinking the classic tools used in strategic planning, in order to diminish the Strategy Execution GAP and to help companies achieving better results.